MENJAGA AKHLAK DI WAKTU SENJA: PERSEPSI MASYARAKAT TERHADAP PROGRAM MENGAJI SEBAGAI GERAKAN MORAL ANAK DI DESA NGASEM KECAMATAN NGAJUM - Annida Amilatud Dinillah; Ahmad Fauzi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyze the community’s perception of the after-Maghrib Quran learning program in Ngasem Village and to examine its effectiveness in shaping children’s religious character and preventing moral decline. This research employed a qualitative approach with a case study design, using in-depth interviews, field observations, and documentation as the main data sources, which were then analyzed using Miles and Huberman’s interactive model. The findings reveal that the community perceives the program very positively because it strengthens children’s Quran literacy, nurtures discipline, and improves their behavior. Although the program has not yet been formalized through a Village Regulation, it continues to run effectively due to strong community engagement, the active role of Quran teachers, and the village’s religious environment. Children show high enthusiasm through regular attendance and positive learning attitudes. Beyond individual benefits, the program also enhances social cohesion, cultivates a religious atmosphere, and serves as an essential form of community-based nonformal education